2017
DOI: 10.5114/aoms.2017.68942
|View full text |Cite
|
Sign up to set email alerts
|

Five gene variants in nonagenarians, centenarians and average individuals

Abstract: IntroductionGenetic factors contribute to the variation of human life span which is believed to be more profound after 85 years of age. The aim of the present study was to evaluate the frequency of 5 gene polymorphisms between nonagenarians, centenarians and average individuals.Material and methodsSingle nucleotide polymorphisms (SNPs) of telomerase reverse transcriptase (TERT; rs2736098), insulin-like growth factor-1 binding protein-3 (IGFBP3; A-202C, rs2857744), fork-head box O3A (FOXO3A; rs13217795 and rs27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It is used to treat solid tumors, lymphomas and sarcomas with a high degree of malignancy [ 2 ]. Single nucleotide polymorphisms (SNPs) in genes that encode antineoplastic drug-metabolizing enzymes could have effects on drug efficacy, toxicity and life span [ 3 5 ] . The CYP2B6 gene has more than 29 SNPs, but only CYP2B6*2 and CYP2B6*6 are functionally significant and result in decreased enzyme activity [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat solid tumors, lymphomas and sarcomas with a high degree of malignancy [ 2 ]. Single nucleotide polymorphisms (SNPs) in genes that encode antineoplastic drug-metabolizing enzymes could have effects on drug efficacy, toxicity and life span [ 3 5 ] . The CYP2B6 gene has more than 29 SNPs, but only CYP2B6*2 and CYP2B6*6 are functionally significant and result in decreased enzyme activity [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…. In humans, exceptional longevity-associated FOXO3A polymorphisms have been identified in multiple cohorts (Kenyon 2010;Joshi et al 2017;Kolovou et al 2017), and NRF2 activation and mTOR inhibition have been shown to delay senescence in human fibroblasts (Kapeta et al 2010;Walters et al 2016). As proof of concept, genetic screens for organismal stress resistance in yeast, worms and plants have enriched for mutants that live long (de Castro et al 2004;Kim and Sun 2007;Kennedy et al 1995;Cao et al 2003).…”
mentioning
confidence: 99%
“…Even though we found no association between ACE genotypes and age-related differences, we add value to the literature in that studies of this ACE polymorphism had not been studied in relation with longevity in a Peruvian sample before. In addition, few studies have described the relationship of the ACE polymorphism in groups under 85 years old (Forero et al, 2006;Kolovou et al, 2014). Although studies of the longevity phenotype are mostly focused on nonagenarians and centenarians, studies of genetic characteristics of younger subgroups are important to study ageing trends in the prevalence of the ACE genotypes.…”
Section: Discussionmentioning
confidence: 99%